2018
DOI: 10.1038/s41598-018-27961-6
|View full text |Cite
|
Sign up to set email alerts
|

Bryozoans are Major Modern Builders of South Atlantic Oddly Shaped Reefs

Abstract: In major modern reef regions, either in the Indo-Pacific or the Caribbean, scleractinian corals are described as the main reef framework builders, often associated with crustose coralline algae. We used underwater cores to investigate Late Holocene reef growth and characterise the main framework builders in the Abrolhos Shelf, the largest and richest modern tropical reef complex in the South Western Atlantic, a scientifically underexplored reef province. Rather than a typical coralgal reef, our results show a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…In the present work, we characterized the RBs and surrounding biogenic formations as bryozoans and reefs covered by CCA. Bryozoans were also found previously as the dominant group building the Abrolhos Bank pinnacles in Brazil [62]. Our study identified bryozoans as the main component between depths of 35 and 50 m on the DRS.…”
Section: Discussionsupporting
confidence: 83%
“…In the present work, we characterized the RBs and surrounding biogenic formations as bryozoans and reefs covered by CCA. Bryozoans were also found previously as the dominant group building the Abrolhos Bank pinnacles in Brazil [62]. Our study identified bryozoans as the main component between depths of 35 and 50 m on the DRS.…”
Section: Discussionsupporting
confidence: 83%
“…The Abrolhos Bank (16°40′–19°40′ S, 39°10′–37°20′ W) comprises a 40,000 km 2 benthic mosaic of reefs, rhodolith beds and unconsolidated sediments, encompassing the largest and richest reefs within the South Atlantic ( Moura et al, 2013 ). The reefs are remarkable for their mushroom-shaped pinnacles with flat tops, which result in strong habitat variation at relatively small spatial scales (pinnacles’ walls and tops) ( Bastos et al, 2008 ). Pinnacles are dominated by massive and encrusting corals, reaching up to 30% of the benthic cover ( Francini-Filho et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Where they occur, these extensive algal build‐ups constitute an important component of the MEs, with the coalescence of rhodoliths having been hypothesized as a possible mechanism for the formation of carbonate reefs (Amado‐Filho et al., ). In fact, many Brazilian biogenic reefs are primarily formed by the growth of calcareous red algae, bryozoans, milleporids and scleractinian corals (Bastos et al., ; Leão et al., ).…”
Section: South Atlantic Mesophotic Ecosystemsmentioning
confidence: 99%